PRODUCTIVE PERFORMANCE OF JERSEY X SAHIWAL COWS IN CHITTOOR DISTRICT OF ANDHRA PRADESH (Indian Journal of Animal Production and Management, 2013)
Season of birth and age at sexual maturity had a non-significant effect on first lactation milk yield. The overall least-squares mean lactation milk yield was 2154.07 ± 16.88 liters (Lt). Significant effect of batch was found on first lactation milk yield in the present study. Cows belonging to 4th batch recorded significantly (P
Keywords: Progeny Testing Programme; lactation milk yield; peak yield; age at sexual Maturity